2019
DOI: 10.3390/su11113070
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Long-Term Trends in the Anthropogenic Night Sky Brightness

Abstract: Monitoring long-term trends in the evolution of the anthropogenic night sky brightness is a demanding task due to the high dynamic range of the artificial and natural light emissions and the high variability of the atmospheric conditions that determine the amount of light scattered in the direction of the observer. In this paper, we analyze the use of a statistical indicator, the mFWHM, to assess the night sky brightness changes over periods of time larger than one year. The mFWHM is formally defined as the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…Two main and complementary approaches are commonly used: (a) tracking the changes of the emitted artificial radiance by means of ground-based measurements [21][22][23], airborne surveys [24][25], or remote sensing from Earth orbiting platforms [26][27][28][29][30][31], and (b) monitoring the evolution of the night sky brightness using specific detectors [32][33][34][35][36][37][38][39], CCD and general purpose DSLR cameras [40][41][42][43], and even by means of comprehensive citizen science observations [44]. Different trends have been reported, sometimes apparently at odds with each other, including a sustained increase of the radiance and overall lit surface around the world, at an estimated 2% yearly rate [45], and a tendency to darker readings in the long-term series recorded by ground-based night sky brightness detectors [46][47], whose progressive aging has not been discarded as a potential cause.…”
Section: Introductionmentioning
confidence: 99%
“…Two main and complementary approaches are commonly used: (a) tracking the changes of the emitted artificial radiance by means of ground-based measurements [21][22][23], airborne surveys [24][25], or remote sensing from Earth orbiting platforms [26][27][28][29][30][31], and (b) monitoring the evolution of the night sky brightness using specific detectors [32][33][34][35][36][37][38][39], CCD and general purpose DSLR cameras [40][41][42][43], and even by means of comprehensive citizen science observations [44]. Different trends have been reported, sometimes apparently at odds with each other, including a sustained increase of the radiance and overall lit surface around the world, at an estimated 2% yearly rate [45], and a tendency to darker readings in the long-term series recorded by ground-based night sky brightness detectors [46][47], whose progressive aging has not been discarded as a potential cause.…”
Section: Introductionmentioning
confidence: 99%
“…In short, these statistical selections are the other ways of selecting clear and moonless data that represent the true value of night sky brightness. e stability of sky brightness during the whole night becomes the main key to the selections both in the studies by Bará et al [35,36] or in the study reported here. e difference is that Bará et al [35,36] used statistical approaches to the density distribution constructed using long term data while the current study evaluates nightly characteristics to determine the class.…”
Section: Classification Performancementioning
confidence: 58%
“…e stability of sky brightness during the whole night becomes the main key to the selections both in the studies by Bará et al [35,36] or in the study reported here. e difference is that Bará et al [35,36] used statistical approaches to the density distribution constructed using long term data while the current study evaluates nightly characteristics to determine the class. For the case of data obtained in tropical region where the clear sky fraction is somewhat lower [37], there is a caution that the sharp distribution of the ideal data is likely to be overwhelmed (or smoothed) by data obtained during cloudy or overcast conditions.…”
Section: Classification Performancementioning
confidence: 58%
See 1 more Smart Citation
“…Light pollution poses a significant threat to our health, the dark skies, and the natural environment. This fact is backed by extensive research in the fields of medicine, astronomy, and the environmental sciences [59][60][61][62][63][64][65][66][67]. It is imperative to push for measures against light pollution because research regarding its impact on human health has helped make headlines worldwide.…”
Section: Discussionmentioning
confidence: 99%